Analysis of Macroeconomic Factors Affecting Airline Stock Prices - Alıcı, Abdulkadir (ANDULI, Revista Andaluza de Ciencias Sociales, 2024)
Change in stock prices and development of the market vary depending on decisions made by investors. Decisions made by investors are determined by corporate performance, the country’s economic situation, political developments and changes in macroeconomic factors. In this study, the relationship between stock prices of airlines and macroeconomic variables was analyzed. To accomplish this, daily macroeconomic data of 14 airlines covering the years 2009-2018 were analyzed by Toda Yomamato and Hatemi-J asymmetric causality tests, and macroeconomic factors (Brent oil price, dollar exchange rate and interest rate) determining stock prices were identified. According to the results of the Toda and Yomamato causality test, it was found that there was a significant relationship among variables of the dollar exchange rate, the price of oil and stock prices of airlines. Except for one airline, there was no significant relationship between interest rate and stock price. According to the results of the Hatemi-J asymmetric causality test, it was found that there were significant relationships among variables of the dollar exchange rate, oil price, interest rate, and airline stock prices. In light of these findings, innovation and adoption of alternative fuel technology by the aviation industry and airlines can be a successful alternative to oil price risk. Results on exchange rate and interest rate changes indicate that airlines and related governments should focus on policies that increase growth of the aviation industry.